COMPARATIVE-TYPOLOGICAL AND TRANSLATIONAL STUDY OF LITOTA IN ENGLISH AND UZBEK LANGUAGES - Alibekova, Gulchehra (Журнал иностранных языков и лингвистики, 2021)
COMPARATIVE-TYPOLOGICAL AND TRANSLATIONAL STUDY OF LITOTA IN ENGLISH AND UZBEK LANGUAGES